1994
DOI: 10.1006/taap.1994.1109
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Potency of 2,3,3′,4,4′,5-Hexachlorobiphenyl Relative to and in Combination with 2,3,7,8-Tetrachlorodibenzo-p-dioxin in a Subchronic Feeding Study in the Rat

Abstract: Interactive effects on toxicity and biochemical parameters were studied between 2,3,3',4,4',5-hexachlorobiphenyl (PCB 156) and 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) in a 13-week feeding study of female Sprague-Dawley rats. The diets were supplemented with PCB 156 (1.2, 6, or 12 mg/kg), with TCDD (5 micrograms/kg), or with combinations of both compounds. Estimated daily intake of 365 micrograms/kg body wt/day (6 mg/kg diet group) of PCB 156 caused a decrease in body weight gain, thymic atrophy, liver enlar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 0 publications
6
16
0
Order By: Relevance
“…12]. There is some controversy over compound, gender, age, and strain-related factors associated with CYP2B induction [31,32], but our results, showing increased PROD activity in liver microsomes from TCDDtreated rats, are consistent with previously reported observations [33]. The observation that multiple CYPs are inducible by nasal mucosa has several human health implications.…”
Section: Family)supporting
confidence: 95%
“…12]. There is some controversy over compound, gender, age, and strain-related factors associated with CYP2B induction [31,32], but our results, showing increased PROD activity in liver microsomes from TCDDtreated rats, are consistent with previously reported observations [33]. The observation that multiple CYPs are inducible by nasal mucosa has several human health implications.…”
Section: Family)supporting
confidence: 95%
“…At postnatal day 21, there were no observable reductions in plasma T4 levels, indicating that perinatal exposure to PCBs did not cause permanent alterations in thyroid hormone levels in the offspring. Reduced plasma T4 levels were also observed in rat pups born to dams exposed to 4 or 16 mg of 2,3',4,4',5-pentaCB (PCB 118) and 16 or 64 mg of 2,2',4,4',5,5'-hexaCB (PCB 153)/kg/day from gestation day 10 to gestation day 16 (41).…”
Section: Estrogen Receptor-mediated Effectsmentioning
confidence: 93%
“…For example, severely depressed T4 levels (by 60-90%) were observed in fetal and neonatal rats following in utero exposure to 5 or 25 mg of Aroclor 1254/kg from gestation day 10 to gestation day 16 (32), while much higher doses of Aroclor 1254 were needed in adult rats to cause similar changes in plasma T4 levels (36). At postnatal day 21, there were no observable reductions in plasma T4 levels, indicating that perinatal exposure to PCBs did not cause permanent alterations in thyroid hormone levels in the offspring.…”
Section: Estrogen Receptor-mediated Effectsmentioning
confidence: 99%
“…In the case of synergism, the congeners act via multiple mechanisms to produce a greater than additive effect which the TEQ would thus underpredict. Van Birgelen et al (42) found clear evidence of synergism for increases in both hepatic and urinary porphyrins as well as significant decreases in total T4 (36,43).…”
Section: Discussionmentioning
confidence: 99%